Analysis of Motivation Level of Student Physical Activity in Pandemi Covid-19 Bandung - Iskandar Muda Bachtiar (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2022)
Motivation of student physical activity is very influential to carry out student physical activities in this Pandemic period. This study aims to describe the motivation of the physical activity of students in the Covid-19 Pandemic in Bandung. The research method used is a quantitative descriptive method. The population in this study were high school students in Bandung. The sample in this study was students who were quarantined at home during the Covid-19 Pandemic period in Bandung as many as 301 high school students in Bandung. In returning the sample, researchers used cluster sampling. This study uses the Sport Motivation Scale Institute. Data analysis uses the Statistics Kolmogrov Smirnov test for testing data normality and Mann Whitney and Kruskal Wallis tests to find out the difference between the sexes and the city of Bandung. In this study proves that there is a difference between the motivation of the physical activity of male and female students and the difference between regions in the city of Bandung. The results of the analysis show that there is a difference between the level of motivation of the physical activity of male and female students and based on the territory in this pandemic period.